Analisis Pengelolaan Tata Letak Gudang Pada Perusahaan (Third Party Logistik) Dengan Metode Sistem Layout Planning (SLP) - Dzaky, Muhammad Naufal; Rizaldy, Wynd; Yulianto, Yuda; Puspita, Sesaria Mardhiani Rachma; Noviansyah, Denny (Institut Transportasi dan Logistik Trisakti, 2023)
PT. X is a company engaged in logistics, especially as a third party that provides services in the form of warehouse rental. As well as storage warehouses that are used to accommodate new goods from vendors to overcome all logistics in shipping goods. Based on the analysis carried out directly at the warehouse location, it was found that there was a problem regarding the accumulation of goods that came in the staging area , due to the location of forklift storage that was far from the location in the warehouse to the proposal to minimize material handling costs. With these problems, an analysis of the layout proposal based on data was carried out using the System Layout Planning (SLP) method, the result of the proposal was aimed at minimizing the costs incurred by the company and reducing the distance in the material handling flow. In this case, the calculation using System Layout Planning (SLP) obtained the results of changes regarding material handling costs, the change was initially Rp. 2,612,245 and the proposed material handling cost saved Rp. 559,251 to Rp.2,052. 994 and for the distance obtained the result After the implementation of the proposed layout, the material displacement flow distance / week was 23065m from the initial layout of 25326m and there was a difference of 2,261m. With the implementation of these changes, researchers hope that companies can achieve better operational efficiency and optimize the use of existing resources.